Comportamiento agronómico y valoraciónnutricional de la asociación de matarratón (Gliricidia sepium) con pasto saboya (Panicum maximun), y pasto brachiaria decumbens (Brachiaria decumbens). - Mora Saltos, Manuel Antonio (2012)
In the property “María” of the Technical State University of the canton Quevedo, located in the km 7 of the Road Quevedo. The Connection, county of Ríos, county of Ríos was determined the agronomic “Behavior and nutritional value of the association of Matarratón (Gliricidia sepium) with grass Saboya (Panicum aximum) and grass Brachiria (Brachiaria decumbens)” in different states of maturity, where they took as objectives to analyze the agronomic behavior of the gramineous-leguminous associations and to carry out the analyses bromatológicos to determine the nutritional value, using a design of complete blocks at random (DCA). In the simple effect of the grass, the association Matarratón with grass Saboya obtained the best indexes in the variables forage (159,18 g) weight, weight of leaves (61,97 g), shaft (81,00 g) weight and relationship leaves aérea: parte radicular (1,34). And in the simple effect of the ages the highest results in almost all the variables excepting the relationship leaves aérea:parte radicular they corresponded to the age of 110 days. In the interaction of the associations for the ages, the best indexes in forage (200 g) weight, weight of leaves (85,55 g), shaft (92 g) weight and relationship leaves aérea: parte radicular (1,63 kg), they register to the 80 and 110 days in the association of Matarratón with the grass Saboya; and the best root (232,65 g) weight, and relationship hoja: tallo (1,23) with the association of Matarratón with grass Brachiaria also to the 80 and 110 days. The protein greater levels were obtained with the association of Matarratón with grass Saboya to the 80 and 110 days with the 14,50 and 14,20%. And the lowest fiber level is reported in the association of Matarratón with grass Brachiaria to the 80 days with 7,92%. For the composition microbiológica at 80 140, the populations higher days, of bacterias, mushrooms and fixers of N asimbiótico showed up with the association of Matarratón and grass Saboya; and the biggest actinomicetes population, celulolíticos and solubilizadores of P in the association of Matarratón with the grass Brachiaria. The bigger than colonization percentage and endófitos density showed up to the 80 and 140 days in the association of Matarratón with the grass Saboya. For the obtained results the outlined hypotheses were confirmed: “The nutritious value of the gramineous-leguminous association Matarratón with grass Saboya for the two court ages will be superior” and “The gramineous-leguminous association Matarratón (Gliricidia sepium) more grass Saboya (Panicum aximum) will show the biggest production of biomass in the different states of maturity.”